Selective extraction of trivalent actinides using CyMe4BTPhen in the ionic liquid Aliquat-336 nitrate. Issue 11 (3rd February 2021) - Zsabka, Péter; Van Hecke, Karen; Adriaensen, Lesley; Wilden, Andreas; Modolo, Giuseppe; Verwerft, Marc; Binnemans, Koen; Cardinaels, Thomas
Abstract : Improving the kinetics of selective An(iii ) extraction from nitric acid feed solutions into an ionic liquid based solvent: combining CyMe4 BTPhen with TODGA in Aliquat-336 nitrate. Abstract : The extraction of Am(iii ), Cm(iii ) and Eu(iii ) by 2, 9-bis(5, 5, 8, 8-tetramethyl-5, 6, 7, 8-tetrahydro-1, 2, 4-benzotriazin-3-yl)-1, 10-phenanthroline (CyMe4 BTPhen) from nitric acid solution was studied using the ionic liquid Aliquat-336 nitrate ([A336][NO3 ]) as diluent. Results show a high selectivity of the solvent for Am(iii ) and Cm(iii ) over Eu(iii ), but rather slow extraction kinetics. The kinetics of CyMe4 BTPhen were largely improved by the addition of 0.005 mol L −1 N, N, N ′, N ′-tetra- n -octyl-diglycolamide (TODGA) as a phase transfer reagent and by the use of 1-octanol as co-diluent. The addition of the phase transfer catalyst and co-diluent did not compromise the selectivity towards the actinide/lanthanide separation and thus this four-component system can be successfully applied to separate Am(iii ) and Cm(iii ) from the lanthanides.